Investigation of Nonlinear Behavior of Composite Bracing Structures with Concrete Columns and Steel Beams (RCS) Applying Finite Element Method - Ali Kheyroddin; Mohamad Ali Kafi; Fahime Eskandariyan; Zeinab Madah (Mechanics of Advanced Composite Structures)
The composite structural system (RCS) is a new type of moment frame, which is including a combination of concrete columns (RC) and steel beams (S). These structural systems have the advantages of both concrete and steel frames [1]. In previous research on composite structures, there are some studies regarding RCS composite conections, but there is no investigation about seismic resisting system for these systems in aspect of implementation and performance. In this paper, it is investigated about the seismic behavior of the RCS composite bracing frame. To achieve this objective, nonlinear analysis of RCS composite frames with and without bracing has been done using finite element method. The behavior factors of these frames have been calculated after analyzing frames. It can be seen based on the results of the analysis that braces increase the yielding strength, ultimate strength and stiffness of RCS composite frames. Also, the comparison of analytical and experimental results shows that the nonlinear behavior of RCS can be accurately predicted using finite element method.